Pengaruh Pemberitaan Kompas.Com Terhadap Sikap Pemilih Pemula di Universitas Garut - Mustopa, Ridwan; Adnan, Iis Zilfah; Azzahra, Nedia (STAI Bumi Silampari, 2024)
This study examines the influence of Kompas.com news on the attitudes of novice voters at the University of Garut concerning the Constitutional Court's decision on the age limit for candidates in the 2024 presidential election. The Constitutional Court's decision has sparked widespread public debate, particularly among novice voters. Given their need to understand the issue, these voters often turn to news platforms like Kompas.com, which has published over 100 articles on the subject. The study employs a quantitative research method with a descriptive approach. The sample comprises 97 novice voters from the University of Garut, selected using the purposive sampling technique. Data collection involved distributing questionnaires, while analysis included research instrument tests, linear regression analysis, and hypothesis testing. Results indicate that Kompas.com news significantly impacts voters' cognitive attitudes, with an average score of 76.9%, categorized as